CHARACTER EDUCATIONAL MANAGEMENT IN IHYA ULUMUDDIN: AL GHAZALI’S PERSPECTIVES - Abdurrahman, Abdurrahman; Anggarini, Ida Fitri (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Character education is a necessity that must be carried out in Indonesia for three reasons such as ideological, philosophical, and normative reasons. This is because the development of human resources in Indonesia must be based on the nation's noble ideals based on Pancasila values. One of the initial contributions of character education in Indonesia was education organized by Islamic boarding schools for a long time. In it, there is an in-depth study related to the inculcation of character values, namely the ideas related to educational management conveyed by Al-Ghazali in Ihya Ulumuddin. Among these ideas is attention to important aspects of management functions ranging from planning implementation to job evaluation. This study uses a concept analysis method to understand and describe the idea of character education management conceptually from Al-Ghazali's perspective in Ihya Ulumuddin. The analysis was carried out through a concept advancement approach, to obtain a scientific definition directly integrated with the conceptual framework according to empirical reality. It is hoped that this approach can translate Al-Ghazali's ideas which tend to be moral-Sufi into a broader educational management framework. Based on the variations of educational management functions offered by experts, Al-Ghazali offers a hexalogy of management functions, namely; 1) Musyarathah which consists of planning, organization of resources, time management, and the formulation of performance indicators. 2) Muraqabah, namely systematic monitoring and actualization of performance indicators. 3) Muhasabah, consists of reporting, self-evaluation, and supervision from superiors to an evaluation of work programs. 4) Mu'aqabah, namely reward and punishment must be carried out to maintain the stability of the series of the three previous functions. 5) Mujahadah and 6) Mu'tabah, namely a motivation to always improve the quality of targets and levels of performance indicators with a spirit of dissatisfaction with the results that have been achieved.